دور الكتاتيب القرآنية (الخلاوى) في محو الأمية عبر تعليم اللغة العربية في نيجيريا: Role Of Tsangaya (Almajiri) Schools on Illiteracy Alleviation in Nigeria - Garba, Ahmad (SIBAWAYH Arabic Language and Education, 2024)
إن المدارس القرآنية أو الخلاوى المعروف باسم مدرسة تسانغايا (tsangaya) نظام قديم في التاريخ الإسلامي، تمشي جنبا بجنب مع تاريخ نزول القرآن الكريم، وتُعد في الدول الأسلامية وفي نيجيريا خصوصا أول مدارس بعد المنزل يتعلم فيه الأطفال كتاب الله العظيم ومبادئ الدين الإسلامي، وكان لها أكبر الأثر في الحفاظ على اللغة العربية وانتشارها بين جميع الأعراق المسلمة؛ كما تساعد بشكل كبير في محو الأمية بين الشعوب، وهي المراكز الأساسية لتعليم مهارة القراءة والكتابة العربية منذ فترة طويلة، وذلك قبل الاستعمار البريطاني في المنطقة، وبعد مجيء التعليم الغربي صارت الإنجليزية لغة رسمية للدولة تُستعمل في المناهج التعليمية العامة، وهذا مما أنسى أو يكاد يُنسي المجتمع دور الكتاتيب في تثقيف أفراده مبادئ القراءة والكتابة العربية والتي تمثل دورا إيجابيا في تعليم الدين الإسلامي، ولهذا الغرض تهدف هذه الورقة السعي إلى إبراز دور الكتاتيب القرآنية في نيجيريا، وذلك في تعليم اللغة العربية، وخاصة فيما يمس تعليم مهارتي  القراءة والكتابة على المستوى التقليدي، كما ستعرض هذه الدراسة بعض الأدوار التي تلعبها هذه الخلاوى القرآنية في محو الأمية بين الشعوب، ثم المشاكل التي تواجه هذه المدارس مع ذكر بعض الحلول المتمثلة، وكما وصلت نتيجة هذه الدراسة في أن للعلماء الكتاتيب في  نيجيريا إسهامات قيمة جدا في تعليم الأطفال أمور دينية ودنيوية. Generally, in Islamic countries and in Nigeria in particular, Tsangaya schools are considered the first schools after the home in which children learn Qur'an and some principles of Islamic religion, it has the greatest impact in preserving the Arabic language and spreading it among all Muslim ethnicities. tsangaya schools have been the main centers for teaching Arabic reading and writing skills for a long time even before British colonialism in the region, however, after the advent of Western education, English became the official language in Nigeria and is used in the general educational curricula. This is what made society almost forget, the roles of tsangaya schools in the society, which represents a positive role in teaching the Islamic religion. For this purpose, this paper aims to highlight on the roles of tsangaya (Quranic) schools in Nigeria in teaching Arabic and Islamic civilization, especially with regard to teaching reading and writing skills through classical methods. As well as its process on alleviating illiteracy in the society, This study will also present some of the problems facing these schools, alongside some solutions, where as the result of this study revealed that teachers of tsangaya schools have given a very valuable contributions in Nigeria towards teaching religious matters, ethics and moral values to the societies.Keywords: Tsangaya school, Illiteracy alleviation, Skills, Teaching, Nigeria